(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2014)
Abstract: Sought the search to find out what small businesses, the importance of funding, and the role of funders in supporting such projects, which have been addressed in the search through a sample of government banks (Rafidain and Rasheed) and private banks (the Middle East, the Gulf, North, Assyria) and a sample of Small projects borrowed from these banks, but in order to achieve that rely researchers on scientific methods discreet marked by the curriculum descriptive analytical method which is based on the compilation of facts and information then collated and analyzed to reach acceptable results, as well as data collection tool (checklist) was whereby examine questions of a sample of small projects having been selected sample intentional projects borrowed from the government and private banks for the province of Baghdad amounted to (70) projects, distributed on each bank of banks sample six of (10) projects, as well as (10) projects from start-ups funded by the Rafidain Bank within the program concessional loans to the Ministry of Labor and Social Affairs. It built research on the fundamental assumption that (lead granted funding from government and private banks in accordance with the procedures to support small projects through the operation and development and the achievement of employment). It was to prove this hypothesis and to reach a set of conclusions, including: The proportion of loans granted to small enterprises of the total loans and advances to banks, the percentage is low and does not represent the required support of these banks, while we find that the loans granted by the government and private banks have reflected positively on the work project and then run the project, develop and achieve employment. Search also took a set of recommendations including: State-owned banks should be working on the development of specialized lending unit assume the functions of lending to small businesses, and the need to create the necessary funds to support small projects, whether these funds from public budgets of the state or from international donors.